Vloga šolskih svetovalnih delavcev v času kulturno-ekonomske krize - Rožman, Laura; Čagran, Branka (Revija za elementarno izobraževanje, 2014)
The Role of School Counsellors during the Cultural and Economic Crisis. In the article we focus on the role of school counselling services in solving the cultural and economic crisis. In the theoretical part we first define the tasks, roles and meaning of school counselling service or of school counsellors, and the meaning of the terms cultural and economic crisis. We see social responsibility as a way out of the crisis. In the empirical part we then present the results of a survey research carried out on this topic among school counsellors in Slovenian basic and secondary schools. The intention of the study was to determine in what ways the school counsellors perceive this crisis, what knowledge they had in the field of work and in what ways they estimate the importance of individual school professional in solving the problem.
Keywords: school social work; cultural and economic crisis; knowledge; social responsibility; qualifications